Strategi Komunikasi Dan Pemanfaatan Teknologi Informasi Dan Komunikasi Dalam Pengembangan Ketahanan Desa Wisata Pada Masa Pandemi Covid-19 Di Cirebon - Subejo Subejo; Nurul Chamidah; Nirmalasari Nirmalasari; Suyoto Suyoto; Sunarru Samsi Hariadi; Muhamad Muhamad; Apredeah Monica Selvi; Dedi Muhammad Siddiq; Khaerudin Imawan; Isamayana Isamayana (Universitas Gadjah Mada, 2021)
The governance of tourism villages, synergy and coordination among tourism village stakeholders that are efficient and effective and strengthening the capacity and support capacity of stakeholders requires a communication strategy for developing tourism villages that is right in line with advances in information technology which have great potency to facilitate various tourism village development activities. In addition, the latest global developments with the Covid-19 pandemic appear to have a significant impact on the development of tourist villages. The study was conducted in three tourist villages in Jamblang District, Cirebon Regency, which have initiated the tourism village since 2016. Several research techniques used were FGD, in-depth interviews and direct interviews with 95 respondents. The study is able to map stakeholders based on status (internal and external) and stakeholders based on the level of interest and contribution (primary, secondary and tertiary). The main relationships between stakeholders include: socialization, training, extension, reports, coordination, promotion and assistance. Formally, there is no communication strategy document available, but related parties have practiced communication according to their interests. New media and several applications or platforms have begun to be used by the community in supporting the development of tourism villages. The development of tourist villages was significantly affected by the Covid-19 pandemic and the existing strategies are not yet adaptive enough to the problems that arise. Several prospective tourism village development strategies include improving infrastructure aspects, human resource capacity, diversifying tourist attractions and strengthening promotions.